Controlled Multi-Dimensional Assembly of Calcium Carbonate Particles with Industrial By-Product Carbide Slag and CO2 - Yuke Shen; Xiaoli Jiang; Chengcai Tang; Wei Ma; Jianyu Cheng; Hongxu Wang; Hongyu Zhu; Lin Zhao; Yagang Zhang; Panfeng Zhao (Nanomaterials)
The utilization of carbide slag, an industrial by-product, as a resource to prepare value-added products has a profound impact not only for sustainable synthesis and the circular economy but also for CO2 reduction. Herein, we report the very first example of the controlled multi-dimensional assembly of calcium carbonate particles at the micrometer scale with industrial by-product carbide slag and CO2. Calcium carbonate particles of distinctly different sizes, shapes, and morphologies are obtained by finely tuning the assembly conditions. This strategy yields diverse assembled structures, including simple cubic, mulberry-like assembled unit, stacked cubic polycrystalline, and rotated polycrystalline structures, using the same starting materials. This innovative approach not only highlights the adaptability and efficiency of utilizing industrial by-products via multi-dimensional assembly but also provides new insights into the potential applications of the resulting calcium carbonate.